Ver a cidade: modelagem da informação para regulação de assentamentos informais - Costa Lima, Mariana Quezado (2017)
This research is based on the need to regulate (establish rules for) the urban form of precarious settlements of informal origin, in order to prevent the deterioration of urban environmental quality. The main question is “what is the role of information modeling in the regulation of informal settlements?” This question reveals three structuring concepts: regulation, informality and information. Informality is emphasized from the urban point of view, as the condition in which the division, use or occupation of urban land do not comply with current regulation. Even though the distinction between the formal and informal city might be directly related to regulation, this work will discuss how much that distinction is intrinsically tied to a symbolic load that both conditions and is conditioned by the lack of information about the informal city. The work will then analyze the role of information modeling – defined as a representation of reality, circumscribed to the attributes and relationships that form a characterization of reality best suited to help understand a given situation – in shaping that regulation. To gauge indicators and establish parameters that adequately measure the specificities of each settlement, it is not sufficient to know how many people live in such settlements and their demarcation: it is necessary to compile data about the urban form of such settlements, about their built environment and to transform this data in information. This research will touch on the technical, political and economic obstacles to conduct this information gathering but will focus on the alternatives to overcome the technical ones. In order to assess some of these alternatives this work studies the methods of measuring the urban form that are more adequate to the specificities of the informal city in order to propose a new method – one based on information modeling. This method will be applied on a case study regarding a group of settlements assigned as Zona Especial de Interesse Social (Special Area of Social Importance, or Zeis in the Portuguese acronym) in Fortaleza – Zeis Bom Jardim. The method will use a system containing geoprocessing and parametric modeling tools. The results of this work show that regulation aimed at increasing the urban quality of informal settlements require, first and foremost, a good understanding of local reality – a goal to which a representation of this reality is fundamental. Information modeling contributes to this by enabling the generation of a wide gamut of urbanistic information from simple geometric data, making it possible to analyze informal settlements not as amorphous, opaque spots but as urban form – as city.